2011
DOI: 10.1016/j.febslet.2011.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Whirly1 translocates from transplastomic chloroplasts to the nucleus

Abstract: a b s t r a c tWhirly1 was shown to be dually located in chloroplasts and nucleus of the same cell. To investigate whether the protein translocates from chloroplasts to the nucleus, we inserted a construct encoding an HA-tagged Whirly1 into the plastid genome of tobacco. Although the tagged protein was synthesized in plastids, it was detected in nuclei. Dual location of the protein was confirmed by immunocytological analyses. These results indicate that the plastidial Whirly1 is translocated from the plastid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 20 publications
4
113
0
Order By: Relevance
“…PTM, a membrane-bound transcription factor that localizes to the chloroplast outer envelope by four transmembrane domains at its C terminus, has been found to be activated by proteolytic cleavage of the transmembrane domains and to transmit multiple retrograde chloroplast signals to the nucleus . In addition, Whirly1 was shown to be dually located in both the chloroplasts and nucleus of the same cell with the same molecular size and to affect the expression of target genes such as PR1 in the nucleus (Isemer et al, 2012). Similarly, it was reported that GFP fusion proteins could be transported from chloroplasts to the cytoplasm upon biotic and abiotic stresses (Kwon et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PTM, a membrane-bound transcription factor that localizes to the chloroplast outer envelope by four transmembrane domains at its C terminus, has been found to be activated by proteolytic cleavage of the transmembrane domains and to transmit multiple retrograde chloroplast signals to the nucleus . In addition, Whirly1 was shown to be dually located in both the chloroplasts and nucleus of the same cell with the same molecular size and to affect the expression of target genes such as PR1 in the nucleus (Isemer et al, 2012). Similarly, it was reported that GFP fusion proteins could be transported from chloroplasts to the cytoplasm upon biotic and abiotic stresses (Kwon et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…1D) exists in the cytoplasm, it is likely that the chloroplast-localized ZmVDEm could be transported back into the cytoplasm. Interestingly, several chloroplast proteins involved in cytoplasm and/or nuclear localization have been reported as retrograde signals to modulate nuclear gene expression (Chen et al, 2010;Sun et al, 2011;Isemer et al, 2012). PTM, a membrane-bound transcription factor that localizes to the chloroplast outer envelope by four transmembrane domains at its C terminus, has been found to be activated by proteolytic cleavage of the transmembrane domains and to transmit multiple retrograde chloroplast signals to the nucleus .…”
Section: Discussionmentioning
confidence: 99%
“…3C) suggested that this nuclear WHY1 resembled the cleaved plastid WHY1 protein (Grabowski et al, 2008;Isemer et al, 2012). Furthermore, WHY1 formed a complex only with the sense DNA strand but not with the antisense DNA strand (Fig.…”
Section: The Why1 Protein Binds To the Promoter Of Wrky53mentioning
confidence: 88%
“…The dual location in plastids and the nucleus of the same cell makes WHIRLY1 an ideal candidate for information trafficking from plastids to the nucleus. The translocation of WHIRLY1 from chloroplasts to the nucleus has been demonstrated recently in studies using transplastomic tobacco plants synthesizing an HA-tagged version of WHIRLY1 at the 70S ribosomes of the organelles [57]. The tagged WHIRLY1 was detected in the nucleus, where it stimulated expression of PR genes [57].…”
Section: The Whirly Family Of Proteinsmentioning
confidence: 86%
“…Plants have a small family of single-stranded DNA binding proteins called WHIRLY that are also involved in the control of defence gene expression [56,57]. Although most plant species have two members, some species including Arabidopsis thaliana have three WHIRLY proteins.…”
Section: The Whirly Family Of Proteinsmentioning
confidence: 99%